Étude épidémiologique prospective des pathologies dans le XV de France féminin de rugby de juillet 2006 à septembre 2010 - Gutierrez, D.; Roque, P.; Bagate, C.; Barizien, N.; El Helou, N.; Sedeaud, A.; Thoreux, P.; Toussaint, J.-F. (Journal de Traumatologie du Sport, 2011)
The objective of this prospective study is to determine the rate of injury on the population of the French women's rugby team. It was conducted over 50 months from July 2006 to September 2010. The medical staff of the French team collected data during training and match exposure. One of the main results of the study is the significant difference in the incidence of injury leading to a sports interruption greater than 8 days between female and male (5.99/1000 hours vs. 42,1/1000 hours). Lower limb injuries represent half of the injuries observed in our study but the articular lesions represent 80.43% of the injuries leading to an interruption superior to 8 days with an incidence of 4.62/1000 hours of exposure per position. This confirms the data found in the medical literature. The ruptures of the anterior cruciate ligament, following a tackle, are the most severe lesions of our study. The forwards had a higher rate of injury than backs. The three positions most exposed to injuries are the nos.8, 9 and 14. The players are most vulnerable when they are being tackled, during the runs and during the rucks. The study described significant differences concerning a much higher number of severe articular lesions, a more significant vulnerability of women in sustained tackles in a match situation and a different exposure of certain position, particularly the scrum-half and the right-wing.